Economic Analysis of Bhendi Cultivation in Tirunelveli District of Tamil Nadu - T. Rajendran (Research Highlights in Agricultural Sciences Vol. 3, 2022)
Bhendi is cultivated for domestic consumption or for local sale in Tirunelveli district of Tamil Nadu. Most farmeRs. are growing Bhendi on a tiny scale and very few farmeRs. on a big scale. The study was focussed on economic analysis of Bhendi cultivation in Tirunelveli district of Tamil Nadu. A multi-stage random sampling technique was followed for selecting the major Bhendi growing blocks in Tirunelveli district viz Sankarankovil and Vasudevanallur. Six villages from each block were selected randomly and ten farmeRs. from each village were selected thus making a total sample size of 120 respondents. The cost of cultivation in case of large farms was higher (Rs. 1,04,184.76) as compared to medium (Rs. 1,02,730.38) and small (Rs. 97,589.69) farms. The cost of cultivation per hectare showed a rising trend with the rise in the farm size. It could be due to the fact that the large farmeRs. incurred more expenditure on modern farm inputs. On an average the value of net income and family labour income per hectare came to Rs. 67,552.29 and 1,17,300.00 respectively on the sample farms of different sizes. The average input-output ratio in Bhendi was worked out to be 1:1.60 on the sample farms. The per hectare Cost A1, Cost A2, Cost B1, Cost B2, Cost C1, Cost C2 and Cost C3 at the overall level were Rs. 82,399.71, 82,399.71, 84,597.71, 89,597.71, 89,747.71, 94,747.71 and 1,04,222.5 respectively.